Remote Acculturation and Physical Activity Among Adolescent-Mother Dyads in Jamaica: A Developmental Dyadic Moderation. (July 2022) - Gillespie, Sarah; Eales, Lauren; Simpson, Dalicia D.; Ferguson, Gail M.
This study examined the associations between remote acculturation to European American culture of the United States (U.S.), and physical activity levels among Jamaican mother-adolescent dyads. Remote acculturation, a modern type of globalization-facilitated acculturation to a distant non-native culture, is a demonstrated risk factor for some health outcomes, but the association with physical activity has not previously been examined. Mothers and adolescents ( N  = 660; 330 dyads) were recruited from schools in Kingston, Jamaica. Actor-Partner Interdependence Moderation Models tested hypotheses about actor and partner effects of U.S. cultural orientation on moderate and vigorous physical activity (MVPA), and the moderation of these effects by developmental stage, socioeconomic status (SES), and gender. We observed a contrast pattern of moderation consistent with increased autonomy granting across adolescence, such that the signs (positive/negative) of the actor and partner effects depended on adolescent developmental stage. The actor effect of adolescents' U.S. orientation on their own MVPA was negative for early adolescents (unexpected) and positive for mid-adolescents (expected); by contrast, the partner effect of mother's U.S. orientation on adolescents' MVPA was positive for early adolescents (expected) and negative for mid-adolescents (unexpected). SES and gender did not moderate the associations. This study contributes to an emerging body of literature on the health correlates of remote acculturation. Our results suggest that whether remote cultural orientation is a risk or protective factor varies based on the health domain in question, developmental stage, the remote culture, and the context.